1999
DOI: 10.1136/bmj.319.7220.1281
|View full text |Cite
|
Sign up to set email alerts
|

Can computerised decision support systems deliver improved quality in primary care?

Abstract: Computerised decision support systems or "expert systems" are computer software systems that are designed to aid clinical decision making. Computerised decision support has been defined as provision of assessments or prompts specific to the patient and selected from a knowledge base on the basis of individual patient data.1 At its simplest this definition will include programs that suggest alternatives for treatment or diagnosis on the basis of a simple algorithm. More complex systems model the likelihood of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 18 publications
(16 reference statements)
1
46
0
Order By: Relevance
“…The application of DSS in the medical domain has been mostly developed to provide physicians with advice on either diagnosis or treatment by means of artificial intelligence (AI) and Bayesian reasoning [21]. Because of the complexity of drug information, DSS demonstrates great potential in the area of medical prescription, however, only a few publications have addressed this issue.…”
Section: Electronic Medical Record Systems and Decision Support Systementioning
confidence: 99%
“…The application of DSS in the medical domain has been mostly developed to provide physicians with advice on either diagnosis or treatment by means of artificial intelligence (AI) and Bayesian reasoning [21]. Because of the complexity of drug information, DSS demonstrates great potential in the area of medical prescription, however, only a few publications have addressed this issue.…”
Section: Electronic Medical Record Systems and Decision Support Systementioning
confidence: 99%
“…The misclassification rate was higher when schizophreniform disorder was considered as the absence of schizophrenia disorder. Schizophreniform disorder is a provisory di-The usefulness and the impact of such systems in medicine are unclear (11,27). In Psychiatry there are additional hindrances such as the lack of valid constructs of mental disorders, the subjective assessment of psychiatric symptoms, schizophrenia as a heterogeneous phenomenon, the absence of biological markers, and finally the absence of a gold standard (5,(28)(29)(30).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, in the UK, which has an extensive computerised primary healthcare sector, the use of computerised decision support systems (CDSS) is not commonplace. 2 Investigating primary care physicians' use of electronic patient records in Norway, Christensen et al concluded that their full potential had not been reached and that problems of integration and functionality needed to be addressed to achieve this.…”
Section: Introductionmentioning
confidence: 99%
“…by engaging and involving patients in decision making regarding their own health care. 2,8 A range of clinical decision tools to assist providers to perform cardiovascular assessment have been developed, validated, and even adapted to hand-held computers to increase their portability. Some cardiovascular decision tools, such as those developed by the New Zealand National Prescribing Service, 9 American College of Physicians (ACP) and American College of Cardiology/American Heart Association (ACC/ AHA), are algorithmic approaches that make direct recommendations about whether to pursue cardiac testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation